Supported Ionic Liquid Phase Materials from 1,8-diazabicyclo[5.4.0]undec-7-ene Based Protic Ionic Liquid and g-C3N4 and TiO2 Nanoparticles: Preparation and Characterization: Supported Ionic Liquid Phase Materials from 1,8-diazabicyclo[5.4.0]undec-7-ene Based (Dhaka University Journal of Science, 2025)
Supported ionic liquid phase (SILP) materials are a novel approach that blend the benefits of heterogeneous support materials and ionic liquids (ILs) by immobilizing an IL film on a solid phase. In an attempt to modify the surface characteristics of nanoparticles, this study explores a simple refluxing method to prepare two novel SILP materials using two supports, graphitic carbon nitride (g-C3N4) and titanium dioxide (TiO2) and a 1,8- diazabicyclo[5.4.0]undec-7-ene (DBU) based protic ionic liquid (PIL), 1,8-diazabicyclo[5.4.0]undec-7-ene-8- ium hydroxide ([HDBU]OH). FTIR spectra showed peaks for N-H stretching mode in the region of 3051-3200 cm-1 indicating the presence of the PIL in g-C3N4-[HDBU]OH and TiO2-[HDBU]OH. The distinctly different UV-visible absorption spectra as reflected in absorption maxima in SILP materials compared to the PIL, [HDBU]OH indicates the formation of new materials. The surface morphology and the size of the particles of the SILP materials were determined from SEM images and DLS measurements. The g-C3N4 nanosheets exhibits significantly cracked surfaces in the SEM image of g-C3N4-[HDBU]OH with average particle size of 9-12 nm. Although significant increase in the surface roughness is noted, the particle size does not change significantly from that of g-C3N4. TiO2 displayed a spherical surface morphology with an increase in particle size from 22 nm to 102 nm for the SILP. [HDBU]OH can interact in various ways with different supports such as g-C3N4 and TiO2 and allows for tailoring size of nanoparticles and surface morphology of the supports in SILP materials.Dhaka Univ. J. Sci. 73(2): 135-142, 2025 (July)